Disciplina, sanção e consenso na administração pública: por uma compreensão do poder disciplinar para além da imperatividade - Daniel Martins e Avelar (2024)
This dissertation is about administrative consensuality in disciplinary matters in the Brazilian legal system (theoretical paper). Its general objective is to analyze the legality of the exercise of disciplinary power by the Public Administration in a consensual way (substitute agreements), in addition to and without excluding the typical imperative form (unilateral application of disciplinary sanction). The specific objectives are to demonstrate that, originally, the Public Administration's model of action was exclusively imperative, focusing on the figure of the unilateral administrative act, but nowadays, due to the evolutionary process of the State and the Public Administration, consensuality appears to be the normal model of action, with the same legal stature as imperative action; to demonstrate that, originally, the discipline of public servants was understood from special relationships of subjection, which ended up creating an exclusively vertical and unequal legal relationship between public servants and the Public Administration, always solved on the basis of unilateralism and imperativeness (unilateral application of disciplinary sanctions); to demonstrate that the legal relations between public servants and the Public Administration have a special legal regime, but not one of special subjection; to demonstrate that both imperativeness and consensuality are compatible with the 1988 Constitution of the Republic and establish the criteria for choosing one or the other in the specific case, according to the legislative conformation; to analyze the fundamental elements of the disciplinary sanction and present the administrative process structured in an adversary system (adversarial) as an essential (unavoidable) requirement for establishing the guilt of the public servant and validating the act of unilateral imposition of a disciplinary sanction; to demonstrate that the public interest pursued in disciplinary matters is neither unique nor presupposed and can only be achieved through the suitable analysis of the actual case, without disregarding the private interests involved; to analyze the concept, the nature and the purpose of substitute agreements and categorize them according to their material content; to interpret the principle of due process of law in an expanded way, beyond adversarial nature procedures, also including collaborative negotiation procedures. The theoretical framework of the research is the book of Eberhard Schmidt-Assman ("The general theory of administrative law as a system: object and foundations of systematic construction"), more precisely in the part that is about the consensual State and the normality of consensual action. The research is based on the dogmatic-legal methodological approach and the legal-comprehensive methodological approach, in six chapters, including the conclusion. In the end, it is concluded that substitute agreements are allowed in the Brazilian legal system, as a substitute for the act of unilateral imposition of disciplinary sanctions, provided that they are preceded by the due process of negotiation and without prejudice to the complementary action imposed by the Public Administration in the appropriate cases.